Clinical trial of EMD 18-140 (estrogenic compound) in the climacteric syndrome - Ramírez Z., Noé (2015)
The results of clinical trial of EMD 18-140 product that is a combination of natural conjugated estrogens for the treatment of climacteric syndrome occurs. The clinical material is constituted by 46 patients with climacteric symptoms varied, with predominance first of vasomotor disorders, second of neuropsychiatric disorders, thirdly other conditions. The trial has been followed by a period longer than six months, being induced beneficial effects after the first month of treatment. They have been increasing and sustaining throughout the treatment period. The EMD 18-140, drug does not cause lesions on liver as evidenced by the respective functional testing, however no favorable evidence from the topographic point of view, as evidenced by the value indices of maturation.